Examination of urine protein in elderly people at posyandu beringin V Kedungwuni Barat Sub-District With The Dipstic Method - Fitria ningsih; Subur Wibowo (Jurnal Kesehatan, 2023)
One indicator that can measure the metabolic processes that occur in the body is through the results of these metabolic wastes. Urine is the result of the body's metabolism excreted through the kidneys. Examination of urine protein needs to be done in elderly people to control kidney conditions so that there is no more severe risk that can lead to failure of a person's kidney function. The purpose of this study was to determine the description of urine protein in elderly people. It was carried out at Posyandu Beringin V, West Kedungwuni Village, Kedungwuni District. The research method used is descriptive research. Examination of urine protein in elderly people obtained results as many as 22 people (91.67%) with negative results while as many as 2 people (8.33%) with positive results (+). The conclusion of this study was that 2 elderly people (8.33%) were positive (+) for urine protein.